2020
DOI: 10.3389/fimmu.2020.00298
|View full text |Cite
|
Sign up to set email alerts
|

Murine Intraepithelial Dendritic Cells Interact With Phagocytic Cells During Aspergillus fumigatus-Induced Inflammation

Abstract: Bogorodskiy et al. Intraepithelial Dendritic Cells Contact Phagocytes phagocytes and clusters. Based on the spatiotemporal characteristics of the interactions between IE-DCs and CD11b + phagocytes, we provide a novel anatomical rationale for the contribution of IE-DCs to controlling the excessive phagocyte-mediated immune response rather than participating in pathogen uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Moreover, tissue fixation is necessary, and, therefore, the analyses are limited to acquisition of the single time points of the infection process. While able to rapidly image whole organs, LSFM has a lower spatial resolution than confocal laser-scanning microscopy, which has been recently used by Bogorodskiy et al (2020) to look at the behaviour of intra-epithelial dendritic cells during A. fumigatus infections [ 40 , 41 ]. This methodology uses a similar lung clearing procedure to that in Amich et al (2020) but coarsely sections the lung into thick slices to visualise the host–pathogen interactions.…”
Section: Are a Fumigatus Spores Deposited In The A...mentioning
confidence: 99%
“…Moreover, tissue fixation is necessary, and, therefore, the analyses are limited to acquisition of the single time points of the infection process. While able to rapidly image whole organs, LSFM has a lower spatial resolution than confocal laser-scanning microscopy, which has been recently used by Bogorodskiy et al (2020) to look at the behaviour of intra-epithelial dendritic cells during A. fumigatus infections [ 40 , 41 ]. This methodology uses a similar lung clearing procedure to that in Amich et al (2020) but coarsely sections the lung into thick slices to visualise the host–pathogen interactions.…”
Section: Are a Fumigatus Spores Deposited In The A...mentioning
confidence: 99%
“…Previously, we demonstrated that upon inflammation, in the conducting airway mucosa, CD11b + cells were mostly represented by the Ly6G + neutrophils (Bogorodskiy et al, 2020). Thus, our present data support the evidence that FluoSpheres suspended in RBD solution (rather than a phosphate buffer) can attract neutrophils to the conducting airway mucosa and facilitate the ingestion activity of these neutrophils.…”
Section: Resultsmentioning
confidence: 97%
“…Transfer of A. fumigatus -pulsed DCs into naive mice has been shown to confer protective Th1 CD4+ T cell responses secreting interferon (IFN)-γ during A. fumigatus infection which decreased fungal burden and enhanced survival [ 298 ]. On the other hand, cDCs may also dampen excessive anti- A. fumigatus immunity, with one study suggesting that lung intraepithelial DCs inhibit clustering of CD11b+ neutrophils via increased efferocytosis of apoptotic neutrophils which accumulate in the lungs, which would help prevent excessive neutrophilic inflammation and subsequent tissue damage [ 299 ]. Ultimately, the discovery of more subsets of cDC1s and cDC2s may give further mechanistic insight into their role in invasive aspergillosis and provide an understanding of how cDCs play opposing roles in promoting Th1 or Th17 inflammation.…”
Section: Interactions Of a Fumigatus With Host Imm...mentioning
confidence: 99%